The relationship of academic procrastination on non-English majors’ English classroom anxiety: a moderated mediation model - Jiang, Feng (Frontiers in Psychology, 2024)
Objective Academic procrastination is negatively associated with English classroom anxiety among non-English major college students. However, current research has less explored the underlying mechanisms. The present study aims to investigate the relationship between academic procrastination and college students’ English classroom anxiety as well as the mediating role of learning engagement and the moderating role of appraisals of intrinsic values. Methods The academic procrastination scale, English classroom anxiety scale, learning engagement scale and appraisals of intrinsic values scale were used to measure 1,079 non-English majors in Jiangsu Province, China. Results (1) There was a significant positive correlation between academic procrastination and English classroom anxiety of non-English majors. (2) Learning engagement plays a part of mediating role between academic procrastination and English classroom anxiety; (3) When the appraisals of intrinsic values are high, the impact effect of learning engagement on English classroom anxiety is greater. Conclusion Academic procrastination can affect university students’ English classroom anxiety through learning engagement, and this relational pattern is modulated by appraisals of intrinsic values. This finding provides an important theoretical basis and practical insights for understanding and intervening in academic procrastination and classroom anxiety among college students.